1998
DOI: 10.1677/joe.0.1570005
|View full text |Cite
|
Sign up to set email alerts
|

Presence and possible role of vascular endothelial growth factor in thyroid cell growth and function

Abstract: Angiogenesis is an important component in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 26 publications
2
48
1
3
Order By: Relevance
“…It is suggested that sunitinib and sorafenib decrease thyroid function by interfering with VEGF function or impairing thyroid blood flow (2,24). In several reports, however, including the present analysis, bevacizumab did not appear to be associated with altered thyroid homeostasis (25,26). Based on this finding, the neutralization of VEGF would therefore have no significant effect on thyroid function.…”
Section: Discussioncontrasting
confidence: 45%
“…It is suggested that sunitinib and sorafenib decrease thyroid function by interfering with VEGF function or impairing thyroid blood flow (2,24). In several reports, however, including the present analysis, bevacizumab did not appear to be associated with altered thyroid homeostasis (25,26). Based on this finding, the neutralization of VEGF would therefore have no significant effect on thyroid function.…”
Section: Discussioncontrasting
confidence: 45%
“…In both cases, it followed a single phase increase that became significant at day 4 of treatment (4.0-and 2.9-fold increase, for Flk1/ VEGFR2 and flt-1/VEGFR1, respectively) and reached a peak at day 12 as previously reported. 29,30 FGF2 protein expression followed the two vascular remodeling phases as well. FGF2 was detected at low levels from day 0 to day 2 of treatment ( Figure 5A), a strong increase occurred at day 3, followed by a subsequent drop at days 4 and 6.…”
Section: Iodine Deficiency Induces Biphasic Changes In the Expressionmentioning
confidence: 96%
“…26 the role of veGF in thyroid signaling is uncertain. 40,41 unlike treatment with antiangiogenic tKis, bevacizumab is not associated with altered thyroid homeostasis. 42,43 other factors, such as platelet derived growth factor α and c Kit, have roles in thyroid homeostasis, but so far no data have been published.…”
Section: Reviewsmentioning
confidence: 98%